M29. SPECIFIC SYMPTOMS IN ADOLESCENCE PREDICT PSYCHOSIS IN THE NORTHERN FINLAND BIRTH COHORT 1986. (18th May 2020) - Palomäki, Johanna; Kerkelä, Martta; Järvelin, Marjo-Riitta; Jones, Peter; Murray, Graham; Nordström, Tanja; Therman, Sebastian; Veijola, Juha
Abstract: Background: A number of psychological symptoms have been found to predict psychosis. Many studies have found no specificity to separate symptoms predicting non-psychotic psychiatric disorders from those predicting psychotic disorders. Prodromal symptoms are non-specific problems often preceding frank psychosis. Previously prodromal symptoms have been studied mainly retrospectively or in high-risk clinical populations. We were able to conduct prospective study comparing adolescent symptoms predicting non-psychotic psychiatric disorders and psychotic psychiatric disorders. Methods: Members of the Northern Finland Birth Cohort 1986 were asked to fill in PROD-screen questionnaire at age 15–16 years. PROD-screen includes 21 items both measuring positive prodromal symptoms, negative prodromal symptoms and general symptoms. We were able to follow 5, 368 participants using Finnish Hospital Discharge Register detecting new hospital treated mental disorders till 30 years. Results: Subjects who developed psychosis had significantly more commonly positive and negative symptoms than subjects without psychiatric disorder or subjects who developed non-psychotic disorder. When comparing separate symptoms in those having psychiatric hospital treatments, we found three positive symptoms and three negative symptoms predicting specifically psychotic disorders. After adjusting for confounders, the symptoms predicting psychosis were: Difficulty in controlling one's speech, behavior or facial expression while communicating, Difficulties in understanding written text or speech heard, Feelings, thoughts or behaviors that could be considered weird or peculiar. Three of the negative symptoms also predicted psychosis: Difficulty or uncertainty in making contact with other people, Lack of initiative or difficulty in completing tasks, Difficulties in carrying out ordinary routine activities (at least one week). Discussion: In this large prospective population sample both positive and negative symptoms in adolescence associated specifically with development of first episode psychosis compared to hospital treated non-psychotic disorders. This finding is in line with the other prospective general population follow-up studies. The main contribution of our study to the literature is that we had the possibility to compare the subjects who developed clinically real hospital-treated psychosis not only to healthy comparison subjects but also to subjects who developed non-psychotic psychiatric disorder.